2003
DOI: 10.1182/blood-2002-09-2944
|View full text |Cite
|
Sign up to set email alerts
|

Identification of thrombin activatable fibrinolysis inhibitor (TAFI) in human platelets

Abstract: Thrombin activatable fibrinolysis inhibitor (TAFI) is a carboxypeptidase B-like proenzyme that after activation downregulates fibrinolysis. Platelets are known to contain antifibrinolytic factors that are secreted during platelet activation. Therefore, the presence of TAFI in platelets was analyzed. TAFI was identified in platelets in a concentration of about 50 ng/1 ؋ 10 9 platelets and was secreted on platelet activation. Thrombin-mediated activation of platelet-derived TAFI resembled that of plasma-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 21 publications
(8 reference statements)
2
106
2
Order By: Relevance
“…Although porcine pancreatic CPB cannot bind to plasminogen or fibrinogen, it is a very good attenuator of fibrinolysis, suggesting that no binding is required for the protection of the clot against lysis. It has also been shown that CPB is, like TAFIa, able to decrease the cofactor function of fibrinogen degradation products of t-PA-mediated plasminogen activation (24,25). So, it is more likely that there are other reasons yet to be identified, which may include a reduced rate of activation and inactivation, why TAFI-CPB-(293-401) is, despite its stability, not a good attenuator of clot lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although porcine pancreatic CPB cannot bind to plasminogen or fibrinogen, it is a very good attenuator of fibrinolysis, suggesting that no binding is required for the protection of the clot against lysis. It has also been shown that CPB is, like TAFIa, able to decrease the cofactor function of fibrinogen degradation products of t-PA-mediated plasminogen activation (24,25). So, it is more likely that there are other reasons yet to be identified, which may include a reduced rate of activation and inactivation, why TAFI-CPB-(293-401) is, despite its stability, not a good attenuator of clot lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid formation of factor Va antagonizes the function of an important natural anticoagulant (TFPI), whereas accelerated thrombin generation likely enhances the function of a natural antifibrinolytic protein (TAFI). Although plasma contains low levels of free TFPI, both TAFI and TFPI are present in human platelets and are secreted following platelet activation (17,18). In addition, a large pool of active TFPI is sequestered on the endothelial surface in vivo (5), so the local concentration of active TFPI in blood clots can be considerably higher than in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…It is produced mainly by the liver as a zymogen (proCPB) and is also detected in platelets (10). Activation of CPB occurs during thrombotic events (11), through the removal of a so-called activation peptide in the N terminus of proCPB (9).…”
Section: Introductionmentioning
confidence: 99%